2012
DOI: 10.1186/1749-8104-7-23
|View full text |Cite
|
Sign up to set email alerts
|

Postembryonic neuronal addition in Zebrafish dorsal root ganglia is regulated by Notch signaling

Abstract: BackgroundThe sensory neurons and glia of the dorsal root ganglia (DRG) arise from neural crest cells in the developing vertebrate embryo. In mouse and chick, DRG formation is completed during embryogenesis. In contrast, zebrafish continue to add neurons and glia to the DRG into adulthood, long after neural crest migration is complete. The molecular and cellular regulation of late DRG growth in the zebrafish remains to be characterized.ResultsIn the present study, we use transgenic zebrafish lines to examine n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 82 publications
8
61
0
Order By: Relevance
“…In mammals, DRG precursor migration proceeds in waves of tens to hundreds of cells, followed by significant apoptosis to produce ganglia that contain the full complement of neurons in neonates. In zebrafish, however, the initial migratory population of NC is composed of only 10-12 cells per somite, of which only one or two cells assume a sensory neuronal fate (Raible et al, 1992;Raible and Eisen, 1994;McGraw et al, 2008;McGraw et al, 2012). This relatively simple developmental pattern makes the zebrafish particularly amenable to the study of the earliest processes of DRG sensory neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, DRG precursor migration proceeds in waves of tens to hundreds of cells, followed by significant apoptosis to produce ganglia that contain the full complement of neurons in neonates. In zebrafish, however, the initial migratory population of NC is composed of only 10-12 cells per somite, of which only one or two cells assume a sensory neuronal fate (Raible et al, 1992;Raible and Eisen, 1994;McGraw et al, 2008;McGraw et al, 2012). This relatively simple developmental pattern makes the zebrafish particularly amenable to the study of the earliest processes of DRG sensory neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…BaP and Enaphthoflavone disrupt dopaminergic and serotonergic systems in the brain of rainbow trout, as revealed by an increase in the turnover of these neurotransmitters , Gesto et al 2009). In addition, as experimental exposure began early in this study (5 dpf), at a time at which neurogenesis was still underway and the nervous system was maturing (Kastenhuber et al 2010, McGraw et al 2012, Souza & Tropepe 2011, the phenotypes observed may reflect this early disruption. Similar effects have been demonstrated following the embryonic disruption of monoamine systems (Dennis et al 2013, Shabanov et al 2005, Silva et al 2013 or early exposure to silver or cadmium (Kusch et al 2008, Powers et al 2011.…”
Section: Discussionmentioning
confidence: 95%
“…During development, sensory neurons are derived from sox10 + neural crest cells and then turn on expression of ngn when they become post-mitotic neurons [24]. So throughout this imaging, animals were exposed to 450 nm laser for the entire z-stack every 20 minutes to photoconvert the Eos protein.…”
Section: Methodsmentioning
confidence: 99%